2018
DOI: 10.1029/2018jc013894
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Dynamics in Wind Wave‐Dominated Shallow‐Water Environments

Abstract: Sediment dynamics driven by waves and currents in shallow-water estuarine environments impacts many physical and biological processes and is important to the estuary-wide sediment budget. Observational restrictions have limited our ability to understand the physics governing sediment entrainment and mixing in these environments. To this end, we use direct numerical simulation to simulate sediment transport processes in shallow, combined wave-and current-driven flows. Simulations are run with depth-averaged cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 71 publications
4
16
0
Order By: Relevance
“…At the bottom of the computational domain, the erodible/depositional boundary condition (Cheng et al, ; Nelson & Fringer, ) is implemented, which is written as ϕwn3Kϕx3=qe+qd1em1emat2.56804ptx3=0, where qe and qd are the erosional and depositional fluxes at the bottom, respectively. Following the continuous deposition formulation (Sanford, ), the depositional flux is modeled as qd=ϕwn3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the bottom of the computational domain, the erodible/depositional boundary condition (Cheng et al, ; Nelson & Fringer, ) is implemented, which is written as ϕwn3Kϕx3=qe+qd1em1emat2.56804ptx3=0, where qe and qd are the erosional and depositional fluxes at the bottom, respectively. Following the continuous deposition formulation (Sanford, ), the depositional flux is modeled as qd=ϕwn3.…”
Section: Methodsmentioning
confidence: 99%
“…We adopt the triple decomposition method (Reynolds & Hussain, ) to isolate the weak downslope gravity current and the organized variations in the turbulent fluctuating flow field. The triple decomposition is applied in a similar manner as other turbulence‐resolving numerical studies for a current‐wave‐fluctuation decomposition (Nelson & Fringer, ). We decompose a variable ψ into a current component ψc, a wave component ψw, and a fluctuating component ψ as follows ψ=ψc)(x3+ψw)(x3;t+ψ)(x1,x2,x3;t. …”
Section: Methodsmentioning
confidence: 99%
“…where z 0 is the bottom roughness and is the von Kármán coefficient. Recent work has suggested that = 0.38 is the most appropriate value for a boundary layer flow (Nagib & Chauhan, 2008), but we chose a constant = 0.41 for consistency with previous studies in South San Francisco Bay (e.g., Bricker et al, 2005;Cheng et al, 1999). The mean velocity profile can be measured with a profiling current meter, and equation (19) can be fit for optimal values of u * and z 0 .…”
Section: Shear Stress Estimation Methodsmentioning
confidence: 99%
“…Numerous models to describe the combined wave‐current bed shear stress have been proposed over the years, and many imply that wave‐current interactions increase the “apparent” bottom roughness and induce additional drag on the flow (Grant & Madsen, ; Styles et al, ; Styles & Glenn, ; You et al, ). However, one recent numerical study suggests that the opposite effect may be seen in estuarine environments with smooth beds; that is, the drag decreases with the addition of laminar waves (Nelson & Fringer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rising water levels have been shown to impact the erosion of shorelines and low-lying areas, with direct consequences for sediment resuspension. Newly flooded areas along the shallow shores of lakes, sandy coastlines and shallow intertidal mudflats are particularly vulnerable to wind-wave action that can remobilize sediments and lead to erosion (Eadie et al, 2008;Fagherazzi and Priestas, 2010;Nelson and Fringer, 2018). Zhang et al (2004) indicated that sandy beach erosion increased by two orders of magnitude with sea level rise, with eroded sediment being resuspended by waves and carried offshore.…”
Section: Discussionmentioning
confidence: 99%